2022
DOI: 10.1038/s41467-022-29773-9
|View full text |Cite
|
Sign up to set email alerts
|

Scalable production of ultrafine polyaniline fibres for tactile organic electrochemical transistors

Abstract: The development of continuous conducting polymer fibres is essential for applications ranging from advanced fibrous devices to frontier fabric electronics. The use of continuous conducting polymer fibres requires a small diameter to maximize their electroactive surface, microstructural orientation, and mechanical strength. However, regularly used wet spinning techniques have rarely achieved this goal due primarily to the insufficient slenderization of rapidly solidified conducting polymer molecules in poor sol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…For this purpose, Tao et al fabricated an ultra-fine PANI fiber (UFPF) with high mechanical properties and charge storage capacity by solventexchange wet spinning. 147 As shown in Figure 5e, the UFPF was used to construct an all-solid OECT to amplify the tiny signals from the spatial dielectric distribution. The high on/off ratio (>10 3 ), relatively high transconductance, and low operating voltage (<1 V) manifested the advantages of this UFPF as an OECT.…”
Section: Acs Applied Electronic Materialsmentioning
confidence: 99%
“…For this purpose, Tao et al fabricated an ultra-fine PANI fiber (UFPF) with high mechanical properties and charge storage capacity by solventexchange wet spinning. 147 As shown in Figure 5e, the UFPF was used to construct an all-solid OECT to amplify the tiny signals from the spatial dielectric distribution. The high on/off ratio (>10 3 ), relatively high transconductance, and low operating voltage (<1 V) manifested the advantages of this UFPF as an OECT.…”
Section: Acs Applied Electronic Materialsmentioning
confidence: 99%
“…In [ 54 ], the authors reported a solvent exchange strategy to prepare ultrafine PANI fibers (UFPFs). The obtained UFPFs had a small diameter below 5 µm, mechanical strength of 1080 ± 71 MPa, a high area capacitance above 1008 mF cm −2 , and a charge storage capacity of 5.25 × 10 4 mC cm −2 .…”
Section: Conducting Polymers As a Charge Transfer Base For Tactile Se...mentioning
confidence: 99%
“…An ultrathin all-solid organic electrochemical transistor (OECT) with less than 1 V driving voltage was examined. It essentially amplified drain-source electrical signals with low power consumption and responded to vertical pressure and horizontal friction forces at different levels [ 54 ]. The all-solid OECT responded to mechanical deformation as a tactile sensor.…”
Section: Conducting Polymers As a Charge Transfer Base For Tactile Se...mentioning
confidence: 99%
“…Moreover, ionic conductive fibers can also be prepared using a continuous spinning strategy . Thus, wet spinning offers excellent prospects for industrial application. …”
Section: Fabrication Strategies For Fiber Electrodesmentioning
confidence: 99%